2022
DOI: 10.3390/app12020590
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma, Platelet-Rich Plasma, and Nitric Oxide Synthesis Inhibitor: Effects Investigation on an Experimental Model on Rats

Abstract: The evolution of reconstructive methods for defects of the human body cannot yet replace the use of flap surgery. Research is still preoccupied with the ideal techniques for offering the best chances of survival of the flaps. In our study, we investigated the effects of cold atmospheric plasma (CAP), N-nitro-L-arginine methyl ester (L-NAME), and platelet-rich plasma (PRP) injectable solutions on flap survival using an in vivo model. Twenty-four Wistar rats (four groups) had the McFarlane flap raised and CAP, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Additionally, it can be manufactured quickly, indefinitely, non-invasively, and using a conventional technique. 219 There is limited research data available on smart dressings in the worldwide so, this could also emerge as a promising field of research in the future. The technological advancement in upcoming smart dressings can indeed help in wound care and real-time diagnosis.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it can be manufactured quickly, indefinitely, non-invasively, and using a conventional technique. 219 There is limited research data available on smart dressings in the worldwide so, this could also emerge as a promising field of research in the future. The technological advancement in upcoming smart dressings can indeed help in wound care and real-time diagnosis.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Their results showed that it has a greater influence on the rate of necrosis in comparison to those other solutions having noted effects. Additionally, it can be manufactured quickly, indefinitely, non‐invasively, and using a conventional technique 219 …”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…The HVE consists of four stainless steel cylindrical subunits, each with a 14 mm diameter interconnected by a copper plate. The GE electrode is represented by a copper plate with a thickness of 1.5 mm, covered with a 0.1 mm thick dielectric layer [62,63]. In order to expose the medium to CAP discharges and to create the PAM, 24 well flat-bottomed cell culture plates (cat.…”
Section: Experimental Setup and Pam Productionmentioning
confidence: 99%
“…Cold atmospheric plasma treatment methods. Plasma is the fourth aggregate state of matter, after solid, liquid, and gaseous, composed of free photons, ions and electrons, and atoms in their ground states or excited with a net neutral charge (Chaple et al 2020;Caba et al 2022). Cold atmospheric plasma has emerged as a new, non-thermal processing technology with proven efficacy in microbial inactivation and extending the product's shelf life (Chaple et al 2020).…”
Section: Technological Strategies Applied To Flours and Starchesmentioning
confidence: 99%